Thursday

April 24, 2014

April 24, 2014

Posted by **Olivia** on Thursday, October 3, 2013 at 10:18pm.

G(y) =

(y − 1)3/

(y2 + 2y)7

- calculus -
**Steve**, Friday, October 4, 2013 at 12:11amAssuming you mean

G(y) = (y-1)^3 / (y^2+2)^7

then just use the quotient rule to get

-(y-1)^2 (11y^2-14y-6) / (y^2+2)^8

**Related Questions**

calculus - You are given the following function. f(x)= (8+x)/(1-8x) (a) Find the...

calculus - Find the derivative of the function using the definition of ...

Calculus - Use a symbolic differentiation utility to find the derivative of the ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Find the intervals on which y=1/(x^2+1)^2 is increasing and ...

calculus - Calculate the derivative of the function. Then find the value of the...

Calculus derivatives - f(a) = a + √a (a) Find the derivative of the ...

Calculus - Find the derivative of the function using the definition of a ...